Hypothermic oxygenated machine perfusion of the human pancreas for clinical islet isolation: a prospective feasibility study. (4th July 2021) - Doppenberg, Jason B.; Leemkuil, Marjolein; Engelse, Marten A.; Krikke, Christina; de Koning, Eelco J. P.; Leuvenink, Henri G. D.
Summary: Due to an increasing scarcity of pancreases with optimal donor characteristics, islet isolation centers utilize pancreases from extended criteria donors, such as from donation after circulatory death (DCD) donors, which are particularly susceptible to prolonged cold ischemia time (CIT). We hypothesized that hypothermic machine perfusion (HMP) can safely increase CIT. Five human DCD pancreases were subjected to 6 h of oxygenated HMP. Perfusion parameters, apoptosis, and edema were measured prior to islet isolation. Five human DBD pancreases were evaluated after static cold storage (SCS). Islet viability, and in vitro and in vivo functionality in diabetic mice were analyzed. Islets were isolated from HMP pancreases after 13.4 h [12.9–14.5] CIT and after 9.2 h [6.5–12.5] CIT from SCS pancreases. Histological analysis of the pancreatic tissue showed that HMP did not induce edema nor apoptosis. Islets maintained >90% viable during culture, and an appropriate in vitro and in vivo function in mice was demonstrated after HMP. The current study design does not permit to demonstrate that oxygenated HMP allows for cold ischemia extension; however, the successful isolation of functional islets from discarded human DCD pancreases after performing 6 h of oxygenated HMP indicates that oxygenated HMP may be a useful technology for better preservation of pancreases. Abstract : Doppenberg and Leemkuil et al . demonstrate clinically relevant human pancreatic islet isolation results, in vitro and in vivo, after six hours oxygenated hypothermic machine perfusion of discarded DCD pancreases during transport.